2019
DOI: 10.1037/fam0000508
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress on empathic accuracy in romantic couples.

Abstract: Accurately understanding the thoughts and feelings of romantic partners, termed empathic accuracy, is critical for optimal relationship functioning. Empathic failure is linked to common reasons couples seek therapy (Doss, Simpson, & Christensen, 2004;Jacobson & Christensen, 1996) and is either implicitly or explicitly a target of many couple therapies (e.g., Jacobson & Christensen, 1996). More specifically, couple therapies target partners' abilities to accurately understand one another preceding and during co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…This process does not give spouses an opportunity to understand how the other person is actually feeling and likely contributes to inaccurate perceptions of the other’s experience. Though this possibility is consistent with the empathic accuracy literature in general (e.g., Crenshaw, Leo, & Baucom, 2019), the current study did not include a test of spouses’ perceptions of one another’s emotional experiences during these conversations, so the role of interpersonal affective perception is speculative at present; it would be valuable for future research to directly test this question.…”
Section: Discussionsupporting
confidence: 65%
“…This process does not give spouses an opportunity to understand how the other person is actually feeling and likely contributes to inaccurate perceptions of the other’s experience. Though this possibility is consistent with the empathic accuracy literature in general (e.g., Crenshaw, Leo, & Baucom, 2019), the current study did not include a test of spouses’ perceptions of one another’s emotional experiences during these conversations, so the role of interpersonal affective perception is speculative at present; it would be valuable for future research to directly test this question.…”
Section: Discussionsupporting
confidence: 65%
“…Yet, our sample was quite comparable to other dyadic laboratory-based studies of empathic accuracy (Sened et al, 2017; e.g. Crenshaw et al, 2019), relied on a powerful within-subjects design, afforded statistical power (.80) to detect medium-sized effects (per guidelines by Cohen, 1992) at an alpha level of .05 8 and is to our knowledge unparalleled for a laboratory-based study of empathic accuracy in married couples from highly diverse backgrounds. Second, the present study focused on empathic accuracy for spouse’s emotions using paradigms widely used in prior work (Gottman & Levenson, 1992).…”
Section: Discussionmentioning
confidence: 64%
“…In this study, mothers reported on their own levels of grief, as well as their perceptions of their partner's grief following their pregnancy loss. While previous studies have demonstrated that women possess better empathic accuracy than men (that is, they are better at accurately assessing the thoughts and feelings of their romantic partner); a recent study has demonstrated that when women are under stress, their empathic accuracy decreases (Crenshaw, Leo, & Baucom, 2019). Pregnancy loss is considered a traumatic stressor, which could have potentially decreased mothers' empathic accuracy, clouding their evaluation of their partner's grief.…”
Section: Discussionmentioning
confidence: 99%